In the Framework of Global Trade, Sustainability and Industry Demand for Innovative Process and Technologies, what kind of Modern “Green” Chemical Engineering is Required for the Design of “the Factory of the Future”? - Jean-Claude Charpentier (International Journal of Petroleum Technology, 2019)
The chemical, petroleum, gas, energy and related industries are today confronted with the globalization of the markets, acceleration of partnerships and demand for innovative process and technologies for economic growth, and they are required to offer a contribution to the fight against environmental destruction and not always sustainable behavior of the today world production. This militates for the evolution of chemical engineering in favor of a modern green process engineering voluntarily concerned by sustainability that will face new challenges and stakes bearing on complex length and time multiscale systems at the molecular scale, at the product scale and at the process scale. Indeed, the existing and the future industry processes are progressively adapted to the principles of the « green (bio) chemistry ». This involves a modern approach of chemical engineering that satisfies both the market requirements for specific nano and microscale end-use properties of competitive targeted green (sustainable) products, and the social and environmental constraints of sustainable industrial meso and macroscale production processes at the scales of the units and sites of production. These multiscale constraints require an integrated system approach of complex multidisciplinary, non-linear, non equilibrium processes and transport phenomena occurring on the different time and length scales of the chemical supply chain. This means a good understanding of how phenomena at a smaller length-scale relates to properties and behavior at a longer length-scale, from the molecular and active aggregates-scales up to the production-scales (i.e. the design of a refinery from the Schrödinger’s equations...). It will be seen that the success of this integrated multiscale approach for process innovation (the 3rd paradigm of chemical engineering) is mainly due to the considerable developments in the analytical scientific techniques coupled with image processing, in the powerful computational tools and capabilities (clusters, supercomputers, cloud computers, graphic processing units, numerical codes parallelization etc.) and in the development and application of descriptive models of steady state and dynamic behavior of the objects at the scale of interest. This modern scientific multiscale approach of chemical engineering « the green approach of process engineering » that combines both market pull and technology push is strongly oriented on process intensification and on the couple green products/green processes “to produce much more and better in using much less”, i.e. to sustainabily produce molecules and products responding to environmental and economic challenges. It will be pointed out that process intensification due to innovative continuous flow process processes (novel process windows) and innovative technologies and new equipment construction technologies (additive manufacturing) will contribute to the design of the eco-efficient “factory of the future ”:i.e. a plant in a shoe box for polymer production or in a mobile banana container platform for small-scale production of specialty chemicals, or more generally modular plants leading to flexible chemical production by modularization and standardization in the pharmaceutical and specialty chemical industries and in a great number of other fields such as materials, petroleum and gas, water treatment and desalination and environmental management, among others.